Persepsi Pada Jingle Shopee Versi Baby Shark (Studi Deskriptif Followers Instagram @Shopee_id) - Dinda Rachma Putri; Diandra Forceila; Lystia Ivana (Sekolah Tinggi Ilmu Komunikasi Inter Studi, 2021)
The more and more trade and service companies causes ever-tougher promotion competition. Therefore, advertising in media becomes indispensable needed. The increased competition in trade spurs the emergence of commercial messages in the form of advertisements. One of the well-known e-commerce companies, Shopee, uses the famous Baby Shark song to be used as the company's jingle ad. Jingle is one of the audio stimuli used in advertising as a support for media activation of a product. The Baby Shark version of Shopee ads must have made a message that will be stored in the minds of the people, but each perception will emerge based on its own reasons. Therefore, this study uses the theory of perception by DeVito. The method used in this study is qualitative, where research will conduct data collection in the form of semi-structured interviews where researchers can more freely conduct interviews with ten informants from Instagram followers on @Shopee_id's account. This study aims to determine the public perception on the Shopee ad version of the Baby Shark version and to find out how perceptions are formed. The results of this study are that the community is more aware of Baby Shark songs compared to Shopee Baby Shark songs and the formation of public perceptions because the song is famous before being made a jingle by Shopee and the ad is broadcast on various media.